Unlocking Creativity: A Mixed-Methods Approach to Interpretingthe Ideas and Significance of Creative Media - Gatya Pratiniyata, Gatya Pratiniyata (Akademi Komunikasi SAE Indonesia, 2025)
Modern culture is much influenced by creative media, which blends art, technology, and communication. By means of a mixed-methods approach comprising qualitative interviews, quantitative surveys, and case studies, this study investigates the ideas and value of creative media. According to the findings, including historical background, media evaluation, creative practice, and research techniques improves the caliber of creative media education. Especially successful in raising students' respect of the development of media and its usefulness in social settings were interactive aspects including virtual museum tours and cooperative projects. Furthermore, the PBL (problem-based learning) method effectively helped pupils to grow in their critical and creative ability. But the studies revealed areas where creative thinking was used poorly, which emphasizes the need of a more interactive education. This study greatly helps to create innovative media courses, so educating students to be competent and flexible professionals in the modern society.